2017
DOI: 10.3389/fphar.2017.00678
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind Study Assessing Changes in Cognitive Function in Indian School Children Receiving a Combination of Bacopa monnieri and Micronutrient Supplementation vs. Placebo

Abstract: Several studies have indicated a chronic cognitive enhancing effect of Bacopa monnieri across different ages and cognitive impairment associated with vitamin and mineral deficiencies in children. Therefore, we investigated the effects of 4-month supplementation with a combination of B. monnieri extract and multiple micronutrients on cognitive functions in Indian school children aged 7–12 years. This was a randomized, double-blind, parallel design, single-center study in which 300 children were randomized to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…When 5-week-old mice were treated daily with BME for 7-28 days from day 0, significant enhancement of the spatial cognitive function in the modified Y-maze test occurred on day 7 but not on day 28. Notably, these results are consistent with clinical studies showing that supplementation with a combination of BME and multiple micronutrients to school children aged 7-12 years for 60 days but not 121 days significantly improved spatial working memory [19]. Furthermore, the treatment of neonatal rats with BME caused improvement in spatial memory performance and memory retention at 2-6 weeks after starting the administration [20].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…When 5-week-old mice were treated daily with BME for 7-28 days from day 0, significant enhancement of the spatial cognitive function in the modified Y-maze test occurred on day 7 but not on day 28. Notably, these results are consistent with clinical studies showing that supplementation with a combination of BME and multiple micronutrients to school children aged 7-12 years for 60 days but not 121 days significantly improved spatial working memory [19]. Furthermore, the treatment of neonatal rats with BME caused improvement in spatial memory performance and memory retention at 2-6 weeks after starting the administration [20].…”
Section: Discussionsupporting
confidence: 86%
“…Neurogenesis in the hippocampal dentate gyrus reportedly plays an important role in cognitive performance [19]. Based on the results described above, daily administration of BME (50 mg/kg/day, p.o.)…”
Section: Determination Of Brdu(+) Cells and Differentiation Of Brdu(+mentioning
confidence: 93%
“…Acute multivitamin supplementation has also been shown to improve contentment and cognitive task performance in adults [8]. In children, multivitamin supplementation for 12 weeks has been shown to increase intelligence [19] and cognitive performance, but not mood [6], whereas 4-month supplementation has been shown to have no effect on cognition [20]. These findings together demonstrate that multivitamin supplementation, particularly those higher in B vitamins, may improve cognition and mood, which might be facilitated by improving brain health, although more targeted investigations into the relationship between B vitamins and neuromarkers of health are required.…”
Section: Introductionmentioning
confidence: 99%
“…79 In contrast, a study reported that supplementation of Brahmi extract and multiple micronutrients twice daily for 4 months did not show a significant impact in improving short-term memory in Indian school children. 80 Despite the safety of Brahmi in animal studies and human trials, no studies regarding its safety in pregnancy, so it should not be used. 81,82…”
Section: Brahmi (Bacopa Monnieri)mentioning
confidence: 99%